Principal’s Leadership in Improving Teacher’s Performance - Hiramsa, Hiramsa; Ahyani, Nur; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2024)
This research is descriptive qualitative with data collection interviews, field observation, and triangulation methods. The important role of a principal in creating a conducive learning atmosphere, to achieve educational goals in schools, is also the task of the principal in designing, striving for, and conditioning the school environment that can motivate all school residents to play an active role in advancing the school. The principal at SD Negeri 9 Lubuk Besar has tried to create a positive school environment that can be seen from the performance of the principal who plays an active role in advancing the school and school residents by participating in the mobilizing school program, being an example for all school residents by actively playing a role in all aspects of activities in the school, the principal has also carried out learning supervision, teacher administration and always provide motivating. Teachers at SD Negeri 9 Lubuk Besar have shown good performance with high discipline, try to create varied and creative learning, have an open attitude actively develop self-skills, and always evaluate and complete teacher administration. Overall, the leadership of the principal of SD Negeri 9 Lubuk Besar can improve the performance of teachers and school residents.